Dissociation of Vesicular Stomatitis Virus and Relation of the Virion Proteins to the Viral Transcriptase - Bishop, D. H. L. (1972)
A procedure has been developed for the sequential removal and purification of the glycoprotein and membrane protein of vesicular stomatitis virus (VSV). Neither of these proteins exhibited transcriptase activity. All of the activity was recovered in the ribonucleic acid (RNA)-ribonucleoprotein complex of VSV, which also has four other minor proteins associated with it. During transcription of 41% of the RNA of a virus preparation, no dissociation of the ribonucleoprotein from the viral RNA was observed.